It's Not About You: A Simple Proposition for Improving Biology Education. Issue 2 (1st October 2014) - Wright, Robin
Abstract: THE Genetics Society of America's Elizabeth W. Jones Award for Excellence in Education recognizes significant and sustained impact on genetics education. Consistent with her philosophy of linking research and education, the 2014 Awardee Robin Wright includes undergraduate students in all of her research. She seeks to teach how to think like and to actually be a biologist, working in teams and looking at real-world problems. She emphasizes a learner-centered model of classroom work that promotes and enhances lifelong skills, and has transformed biology education at the University of Minnesota through several efforts including developing the interactive, stimulating Foundations of Biology course sequence, encouraging active learning and open-ended research; supporting the construction of Active Learning Classrooms; and establishing Student Learning Outcomes, standards that measure biology education. She serves as founding editor-in-chief of CourseSource, focusing national effort to collect learner-centered, outcomes-based teaching resources in undergraduate biology.